2018
DOI: 10.1161/jaha.117.007790
|View full text |Cite
|
Sign up to set email alerts
|

Arachidonic Acid, but Not Omega‐3 Index, Relates to the Prevalence and Progression of Abdominal Aortic Aneurysm in a Population‐Based Study of Danish Men

Abstract: BackgroundAnimal models support dietary omega‐3 fatty acids protection against abdominal aortic aneurysm (AAA), but clinical data are scarce. The sum of red blood cell proportions of the omega‐3 eicosapentaenoic and docosahexaenoic acids, known as omega‐3 index, is a valid surrogate for long‐term omega‐3 intake. We investigated the association between the omega‐3 index and the prevalence and progression of AAA. We also investigated associations between AAA and arachidonic acid, an omega‐6 fatty acid that is a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…Numerous biological factors have been identified that contribute to AAA occurrence, e.g., serum elastin peptides (SEP), plasmin-antiplasmin (PAP) complexes, metalloproteinase-2 (MMP-2), metalloproteinase-9 (MMP-9), P-elastase, cystein C, tissue plasminogen activator (tPA), interferon-gamma (IFN-gamma), tumor necrosis factor alpha (TNF-alpha), interleukin-8 (Il-8), interleukin-6 (Il-6), macrophage migration inhibitory factor (MIF), osteopontin, osteoprogerin, fibrynogen, homocysteine, Staphylococcus sp., Chlamydophila pneumoniae, Treponema pallidum, and arachidonic acid [3]. Moreover, in some cases, biomarkers such as arachidonic acid [4] and MMP-9 [5] have also been evaluated as indicators of possible success of the AAA therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous biological factors have been identified that contribute to AAA occurrence, e.g., serum elastin peptides (SEP), plasmin-antiplasmin (PAP) complexes, metalloproteinase-2 (MMP-2), metalloproteinase-9 (MMP-9), P-elastase, cystein C, tissue plasminogen activator (tPA), interferon-gamma (IFN-gamma), tumor necrosis factor alpha (TNF-alpha), interleukin-8 (Il-8), interleukin-6 (Il-6), macrophage migration inhibitory factor (MIF), osteopontin, osteoprogerin, fibrynogen, homocysteine, Staphylococcus sp., Chlamydophila pneumoniae, Treponema pallidum, and arachidonic acid [3]. Moreover, in some cases, biomarkers such as arachidonic acid [4] and MMP-9 [5] have also been evaluated as indicators of possible success of the AAA therapy.…”
Section: Introductionmentioning
confidence: 99%
“…It would be interesting to test the variation of MCE in two sequential samples of the same small/medium AAA patients at two time points of their follow-up (at least on those who progress and would not require surgery) to evaluate whether the changes in MCE are correlated to changes in aortic diameter. In addition, it is important to note that to obtain correlation with AAA growth or time to surgery, we previously tested the whole VIVA cohort [27,28], so in this case, lack of power could also account for the obtained negative results. However, considering alpha = 0.05 and power = 80%, it was estimated that a difference of 2% in MCE could be detected by studying a minimum of 20 subjects in each group.…”
Section: Discussionmentioning
confidence: 99%
“…The statistical tests were defined a priori and in a similar way as in previous publications. 19,26,27 Nonparametric statistics were used for descriptive and univariate analyses. The assumption of normality of continuous measurements was confirmed by visual inspection of residual log-log plots.…”
Section: Methodsmentioning
confidence: 99%
“…As previously described, predefined logistic regression analysis was used to identify whether the upper tertile pMFAP4 at baseline was independently associated with AAA after adjustment for potential confounders identified in the univariate analyses by a P value below 0.10. 27 Multiple linear regression analysis was used to identify whether the level of pMFAP4 at baseline was independently associated with aneurysmal growth rate after similar adjustment for potential confounders. We constructed a Cox proportional hazard model to study whether AAA patients at the upper tertile at baseline had an altered likelihood of receiving later surgical repair.…”
Section: Methodsmentioning
confidence: 99%